DESAIN KOLAM PEREDAM ENERGI BENDUNG PLAOSAN KABUPATEN SEMARANG - Eric Afrida; Totok Apriyanto; Ratih Pujiastuti (Jurnal Teknik Indonesia, 2023)
Hydraulic aspect of the weir is important factors in planning a stilling basin. Remaining energy on the stilling basin is expected to be as minimal as possible so that scour does not occur on the river bed. Plaosan Weir does not yet have a stiiling basin structure. Therefore it is necessary to recommend the design of stiliing basin.The analysis carried out hydrological analysis, including calculating return period rainfall, flood discharge (Q) using the Haspers method, and calculating Froude number (Fr) to determine pond type. Based on the recommendations for the type of stilling basin, a building design is carried out and also stability of design..From the results of calculation it is obtained that 50-year return period rainfall is 108.68 mm. Planned discharge for 50 years is 186.06 m3/s, and froude number : 4. The appropriate type of stilling basin is USBR Type IV. The pond is planned to have a length of L = 17 m, with a block face width of 0.68 m, height of 1.36 m, distance between front blocks of 1.69 m and total of 13 pieces. The results of stability control analysis during normal water conditions and flood water conditions produce values above the safety factor so that it can be concluded that the design is planned qualify.